2003
DOI: 10.1016/s1010-7940(03)00255-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of avoiding cardiopulmonary bypass in non-elective coronary artery bypass surgery: a propensity score analysis

Abstract: In this experience, off-pump coronary surgery in non-elective patients is safe with acceptable results. Non-elective off-pump patients have a significantly reduced incidence of renal failure, and shorter post-operative stays compared to on-pump coronary artery bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
1
19
1
6
Order By: Relevance
“…Exclusion of these five studies from the analysis resulted in a calculated OR for incidence of AF of 0.81 (95% CI 0.63 -1.03), with heterogeneity of 9.67 ðP ¼ 0:29Þ: Similarly, cold blood cardioplegia was not used in four studies [21,22,29,30] and not reported in one study [33]. When we excluded these five studies from the analysis the calculated OR for incidence of AF changed to 0.59 (95% CI 0.41-0.83), with heterogeneity of 29.06 ðP ¼ 0:0003Þ: Retrograde cardioplegia was used in four studies [23,24,26,32,33] and was not reported in one [33]. On exclusion of these five studies from the analysis the calculated OR for incidence of AF changed to 0.61 (95% CI 0.45-0.84), with heterogeneity of 17.79 ðP ¼ 0:02Þ: Inclusion criteria: 1, informed consent; 2, elective CABG; 3, severe obstructive pulmonary disease; 4, normal ejection fraction; 5, multi-vessel disease; 6, no diffuse coronary disease; 7, no ventricular hypertrophy; 8, no cardiac enlargement; 9, low risk patients; 10, no significant renal dysfunction; 11, LAD lesion equal or more than 70%; 12, associated lesion in the RCA; 13, vessel size .1.2 mm; 14, absence of diffuse coronary disease; 15, stable angina pectoris; 16, moderate ventricular function; 17, non-elective cases.…”
Section: Sensitivity Analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Exclusion of these five studies from the analysis resulted in a calculated OR for incidence of AF of 0.81 (95% CI 0.63 -1.03), with heterogeneity of 9.67 ðP ¼ 0:29Þ: Similarly, cold blood cardioplegia was not used in four studies [21,22,29,30] and not reported in one study [33]. When we excluded these five studies from the analysis the calculated OR for incidence of AF changed to 0.59 (95% CI 0.41-0.83), with heterogeneity of 29.06 ðP ¼ 0:0003Þ: Retrograde cardioplegia was used in four studies [23,24,26,32,33] and was not reported in one [33]. On exclusion of these five studies from the analysis the calculated OR for incidence of AF changed to 0.61 (95% CI 0.45-0.84), with heterogeneity of 17.79 ðP ¼ 0:02Þ: Inclusion criteria: 1, informed consent; 2, elective CABG; 3, severe obstructive pulmonary disease; 4, normal ejection fraction; 5, multi-vessel disease; 6, no diffuse coronary disease; 7, no ventricular hypertrophy; 8, no cardiac enlargement; 9, low risk patients; 10, no significant renal dysfunction; 11, LAD lesion equal or more than 70%; 12, associated lesion in the RCA; 13, vessel size .1.2 mm; 14, absence of diffuse coronary disease; 15, stable angina pectoris; 16, moderate ventricular function; 17, non-elective cases.…”
Section: Sensitivity Analysis Resultsmentioning
confidence: 99%
“…It is important to recognise that two studies selected for our analysis caused significant heterogeneity in our results [25,32]. The first of these reported a significantly higher incidence of post-operative AF in the CPB group (49%) as compared to OPCAB (14%) [25].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another case-controlled trial found that serum Cr levels were significantly lower and CrCl was significantly higher in the off-pump group compared to the on-pump group [16]. Karthik et al [17] constructed a propensity score for risk-adjusted comparison of patients undergoing nonelective on- and off-pump CABG. The incidence of renal impairment, as assessed by an increase in Cr level >1.5 mg/ml, was significantly higher in the on-pump group.…”
Section: Discussionmentioning
confidence: 99%